RELIABILITY OF BACK CONCENTRIC ISOKINETIC MUSCLE TESTING USING BIODEX ISOKINETIC DYNAMOMETER - Sabire Akın; Özlem Öner; Nisa Özberk (Archives of Rheumatology, 2004)
Objective: The aim of this study is to determine the test-retest reliability of back extensor and flexor concentric muscle strength using Biodex isokinetic dynamometer. Material and Methods: 49 healthy men and women volunteers were included. Evaluation was carried out with a Biodex System 3 Pro isokinetic dynamometer. Tests were performed in 3 sessions at a 7 day interval. Intraclass-Correlation-Coefficients were calculated to establish day-to-day repeatability. The protocol consisted of 5 isokinetic concentric contractions at a velocity of 60º/sec and 10 repetitions at a velocity of 120º/sec. Results: Results show very good reproducibility in both movement directions at both velocities. ICC for the back flexor muscle strength at 60 º/sec were 0.88 and ICC for the extensor muscle strength were 0.84; ICC for the back flexor muscle strength at 120 º/sec were 0.85, ICC for the extensor muscle strength were 0.84. Conclusion: The results indicate that isokinetic concentric flexor and extensor muscle strength evaluation with this test protocol is reliable. Biodex isokinetic dynamometer is a reliable tool in the evaluation of back muscular performance.